OPTIMALISASI DISIPLIN KERJA PEGAWAI DI UPT SDN PURWOREJO 1 KOTA PASURUAN - Adiba, Farah; Rangga Puspita, Dyah; Irmayanti, Novianik (STIA MALANG, 2024)
Evaluation is an effort to identify and evaluate aspects of work performance that influence the success of an organization or agency. The performance evaluation system or process plays a very important role in optimalizing and managing human resources in an agency because if it is not communicated well it will affect the success of the agency and also the ability of employees to plan their careers. The aim of this research is to assess the current employee work discipline at UPT SDN Purworejo 1 Pasuruan City and to find out what percentage of employee work discipline is according to employee attendance records monitored at UPT. SDN Purworejo 1, Pasuruan City. In this research, the data analysis used to analyze the data is a descriptive method. This method systematically, factually and precisely describes or describes the relationship between the facts and phenomena studied without statistical calculations. The research sample used was all employees at the UPT SDN Purworejo 1 school, Pasuruan City. Data collection techniques were carried out through guidance and literature review.